2016
DOI: 10.1177/0363546516652114
|View full text |Cite
|
Sign up to set email alerts
|

Are Short-term Outcomes of Hip Arthroscopy in Patients 55 Years and Older Inferior to Those in Younger Patients?

Abstract: Although younger patients had superior HOS outcomes reported at 2 years compared with older patients after hip arthroscopy for FAI, both groups had significant improvement compared with their baseline. These data suggest that carefully selected patients 55 years and older without radiographic arthritis may benefit from hip arthroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 24 publications
0
18
1
Order By: Relevance
“…Up to a half of patients may not achieve a clinically important improvement after surgery; hence accurate patient selection is critical to optimising treatment outcomes. Increasing patient age, higher preoperative patient reported scores, and the presence of osteoarthritis have been identified as having a negative impact on outcome in cohort studies of arthroscopic hip surgery 3334 35 36…”
Section: Discussionmentioning
confidence: 99%
“…Up to a half of patients may not achieve a clinically important improvement after surgery; hence accurate patient selection is critical to optimising treatment outcomes. Increasing patient age, higher preoperative patient reported scores, and the presence of osteoarthritis have been identified as having a negative impact on outcome in cohort studies of arthroscopic hip surgery 3334 35 36…”
Section: Discussionmentioning
confidence: 99%
“…An association between advanced degenerative arthritis and inferior outcomes after hip arthroscopy is well documented [ 4 , 57 , 58 ]. A large meta-analysis of over 6000 hip arthroscopy patients by Harris et al [ 6 ] found that conversion to THA was the most common reason for revision surgery.…”
Section: Inappropriate Indications: Arthritis and Hip Dysplasiamentioning
confidence: 99%
“…Hip arthroscopy has been used successfully as a treatment for both intra-articular [femoroacetabular impingement (FAI), labral tears, chondral lesions, loose bodies, synovial abnormalities, instability, septic arthritis] and extra-articular (snapping iliopsoas tendon/iliotibial band, gluteus tendon tears) conditions. Most published results of hip arthroscopy have reported favorable short and mid-term clinical and radiographic outcomes [ 3 , 4 ]. However, with expanding indications for arthroscopic surgery and the subsequent increasing number of procedures being performed, the burden of refractory pain following hip arthroscopy will likely increase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most common indications for hip arthroscopy is a labral tear with femoroacetabular impingement. Previous studies have noted a conversion to THA following hip arthroscopy between 4 and 25% [19, 24, 25]. Risk factors for failure of hip arthroscopy include obesity, decreased joint space (<2 mm), significant chondromalacia, Tönnis Grade 2 osteoarthritis and remaining unaddressed FAI [24, 26].…”
Section: Introductionmentioning
confidence: 99%